The Influence of NiTi Alloy on the Cyclic Fatigue Resistance of Endodontic Files - Ruiz Sánchez, Celia; Faus Llácer, Vicente; Faus Matoses, Ignacio; Zubizarreta Macho, Álvaro; Sauro, Salvatore; Faus Matoses, Vicente (My University, 2021)
Background: The aim of this study was to analyze the influence of NiTi alloy in endodontic rotary instruments on cyclic fatigue resistance. Methods: One hundred and sixty-four (164) sterile endodontic rotary files were selected and distributed into the following study groups: A: 25.08 F2 ProTaper Universal (PTU) (n = 41); B: 25.06 X2 ProTaper Next (PTN) (n = 41); C: 25.08 F2 ProTaper Gold (PTG) (n = 41), and D: 25.06 ProFile Vortex Blue (PVB) (n = 41). A cyclic fatigue device was designed to conduct the static cyclic fatigue tests with stainless steel artificial root canals systems with 250 ¿m apical diameter, 60° curvature angle, 5 mm radius of curvature, 20 mm length, and 6% (25.06) and 8% taper (25.08). Failure of the endodontic rotary instrument was detected by a single operator through direct observation and was also filmed to allow measurement of the exact time to failure. Results were analyzed using the ANOVA test and Weibull statistical analysis. Results: All pairwise comparisons presented statistically significant differences between the time to failure for the NiTi alloy study groups (p < 0.001), except between the PTN and PVB study groups (p = 0.379). In addition, statistically significant differences between the number of cycles to failure for the NiTi alloy study groups (p < 0.001) were also observed. Conclusions: The NiTi CM-Gold wire alloy of the ProTaper Gold endodontic rotary files resulted in greater resistance to cyclic fatigue than ProFile Vortex Blue, ProTaper Next, and ProTaper Universal endodontic rotary files.